Functional relationship between crop raiding by the savannah elephant and habitat variables of the Red Volta Valley in northeastern Ghana - Adjewodah, P.; Oduro, W.; Asase, A. (Pachyderm, 2012)
We investigated the degree to which crop raiding by elephants in the Red Volta Valley is a function of: the density and diversity of their natural browse, extent of degradation of their habitat, and proximity of crop enclaves to the nearest forest boundary. We assessed 50 m × 5 m quadrats for browse and for agents of degradation (m2 of quadrat area clear-felled, burned, and surface mined), and we adopted records of cropraiding rates in 2000–2002 for correlation with habitat variables. We estimated the distance of affected enclaves from the forest, river and village using GIS; the total size of crop fields in a locale provided an estimate of the extent of cultivation. Using correlation and regression analysis, we examined for each locale the association between rate of crop-raiding incidents and the density and diversity of browse, size of crop fields, and distance of affected enclaves from the forest, river and village. We used a stepwise regression model to establish a functional relationship between crop raiding and the enumerated habitat variables. Second-order jackknife and Michaelis-Menten asymptotic estimators showed that the density and diversity of browse was near optimum. About 99% of the vegetation area sampled was burned, and 0.35 ha of vegetation was clearfelled for firewood. No evidence of mining was recorded. There was a significant inverse association between crop raiding and distance of affected enclaves from the forest, while the association between crop raiding and density and diversity of browse and the extent of degradation were not significant. A stepwise regression model gave a functional relationship between the observed rate of crop-raiding incidents and proximity of crop enclaves to the forest as Y = 25.105 + 3.2 – 9.73X (Y = rate of crop-raiding incidents and X the distance from enclave to the forest boundary). Contrary to speculation, crop raiding in the study area is not influenced by the status of browse, extent of degradation or size of cultivated fields. Thus, mitigation measures should include relocating farms away from forest reserves, while measures aimed at reducing the density of farms or replanting of the forest should be de-emphasized as they will not necessarily reduce crop raiding. © 2012, International Union for Conservation of Nature and Natural Resources. All rights reserved.
Keywords: Enclave; Locale